Psychosocial health in pregnancy and postpartum among women living with - and without HIV and non-pregnant women living with HIV living in the Nordic countries - Results from a longitudinal survey study - Ellen Moseholm; Inka Aho; Åsa Mellgren; Gitte Pedersen; Terese L. Katzenstein; Isik S. Johansen; Diana Bach; Merete Storgaard; Nina Weis (BMC, 2022)
Abstract Background The success of antiretroviral therapy has normalized pregnancy among women living with HIV (WWH) with a very low risk of perinatal transmission of HIV. Despite these advances, WWH still face complex medical and psychosocial issues during pregnancy and postpartum. The aim of this study was to assess differences in psychosocial health outcomes between pregnant WWH, non-pregnant WWH, and pregnant women without HIV, and further identify factors associated with probable depression in the third trimester and postpartum. Methods In a longitudinal survey study, participants were included from sites in Denmark, Finland, and Sweden during 2019-2020. Data was collected in the 3rd trimester, 3 and 6 months postpartum using standardized questionnaires assessing depression, perceived stress, loneliness, and social support. Mixed regression models were used to assess changes over time within and between groups. Logistic regression models were used to identify factors associated with depression in pregnancy and postpartum. Results A total of 47 pregnant WWH, 75 non-pregnant WWH, and 147 pregnant women without HIV were included. The prevalence of depression was high among both pregnant and non-pregnant WWH. There was no significant difference between pregnant and non-pregnant WWH in depression scores, perceived stress scores, or social support scores at any time point. Compared to pregnant women without HIV, pregnant WWH reported worse outcomes on all psychosocial scales. Social support and loneliness were associated with an increased odds of depressive symptoms in the adjusted analysis. Conclusions A high burden of adverse psychosocial outcomes was observed in both pregnant and non-pregnant women living with HIV compared to pregnant women without HIV. Loneliness and inadequate social support were associated with increased odds of depression in pregnancy and should be a focus in future support interventions.